PELATIHAN E-LEARNING BERBASIS MOODLE UNTUK MENINGKATKAN KEMAMPUNAN DOSEN STAIMAS DALAM MENYELENGGARAKAN PEMBELAJARAN ONLINE - Makhda Intan Sanusi (LPPM STAIMAS WONOGIRI, 2021)
The use of e-learning is believed to be able to overcome the limitations of lectures in class and of course provide learning services that can be accessed from anywhere and anytime, especially in the current era, all of which use internet access. The policy of using e-learning at the Islamic Mulia Astuti (STAIMAS) Wonogiri is still relatively new and most of the lecturers do not understand how to use it, and some are still in the process of introducing e-learning. Therefore, this training activity can be carried out for two days at the STAIMAS Wonogiri campus hall by involving STAIMAS Wonogiri lecturers. Activities are carried out in the form of simulations, exercises, and questions and answers. This training material is a guideline for using moodle-based e-learning for lecturers, which consists of setting courses, adding learning resources, adding students to classes in each course, monitoring student learning progress, using forum features, a lot like discussion forums, assignments , quizzes and grade reports. This training activity is said to be successful based on the participants' ability to understand and practice the material and it is proven by their work on the e-learning page. participants also felt that this training was very important because it could improve the skills of lecturers in managing learning through e-learning.